VD_FINDINFO AP / 2010 / 156 vom 7. Dezember 2009 - VD Tribunal cantonal (2009)
TRAVAIL D'INTÉRÊT GÉNÉRAL, SURSIS À L'EXÉCUTION DE LA PEINE, PEINE PRIVATIVE DE LIBERTÉ | 37 CP, 41 CP, 42 CP, 411 let. g CPP, 415 CPP, 448 al. 1 CPP